2020
DOI: 10.1002/cam4.3195
|View full text |Cite
|
Sign up to set email alerts
|

Galangin promotes cell apoptosis through suppression of H19 expression in hepatocellular carcinoma cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…In recent years, natural compounds were widely used in many fields including clinical treatment due to their safety and effectiveness. Many preclinical and clinical studies have confirmed that natural compounds have certain therapeutic effects in various diseases, especially cancers (12,32,37,38). Baicalein purified from Scutellaria baicalensis Georgi is an active flavonoid ingredient, which was reported participating in inhibiting the progression of various cancers (13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, natural compounds were widely used in many fields including clinical treatment due to their safety and effectiveness. Many preclinical and clinical studies have confirmed that natural compounds have certain therapeutic effects in various diseases, especially cancers (12,32,37,38). Baicalein purified from Scutellaria baicalensis Georgi is an active flavonoid ingredient, which was reported participating in inhibiting the progression of various cancers (13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Different miRNA analysis was analyzed by DESeq2. The target gene of miRNAs was derived from miRTarBase (http://mirtarbase.mbc.nctu.edu.tw/index.html) (32) and the network diagram of miRNA and target gene was drawn by Cytoscape. R-Package clusterProfiler (33) was used to analyze the target genes of miRNAs for KEGG and GO enrichment analysis.…”
Section: Construction Of Mirnas Libraries and Mirnas Expression Analysismentioning
confidence: 99%
“…Recently, lncRNAs and miRNAs have been demonstrated to have roles in development of different types of cancer, including HCC ( 18 ). There is evidence that reduced expression of lncRNA H19 leads to inhibition of tumor growth in breast cancer, bladder cancer and colorectal cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that H19 expression suppressed endogenous let-7 while H19 mutant was not related to let-7 ( 17 ). Additionally, reduced expression of H19 induced cellular apoptosis and inhibited cell growth in HCC ( 18 ). However, there is little evidence to suggest that COPB2 expression is associated with lncRNAs and miRNAs in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, galangin inhibits epithelial-mesenchymal transition and angiogenesis of glioma by downregulating CD44 (Chen et al 2019a ). Simultaneously, galangin promotes apoptosis of diverse cancer cells, such as hepatocellular carcinoma cells, ovarian cancer cells and glioblastoma cells (Kong et al 2019 ; Fang et al 2019 ; Zhong et al 2020 ; Huang et al 2020 ). One study suggested that galangin, either alone or combined with insulin, can reduce glucose levels and improve skeletal muscle health in patients with diabetes (Kalhotra and Chittepu 2019 ).…”
Section: Trpcs Antagonistsmentioning
confidence: 99%